SKENARIO PROBLEM-BASED LEARNING SEBAGAI PEMICU PENERAPAN PROMOSI PERILAKU HIDUP BERSIH DAN SEHAT BAGI MASYARAKAT OLEH MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS PATTIMURA - Rumahlatu, Athalya Leonni; Makupiola, Selvya M; Arif, Vika RS; Noya, Farah Christina (BAKIRA: Jurnal Pengabdian Kepada Masyarakat, 2024)
The primary objectives of this study are twofold: first, to implement health promotion initiatives related to PHBS, with a specific focus on waste management and water pollution, and to assess their impact on community health. Secondly, to explore the community’s understanding, attitudes, and practices regarding PHBS, particularly water pollution and its effects on health. Health education serves as the central approach for promoting PHBS. Problem-based learning guides the search for relevant health education materials. Simple interviews were conducted before and after providing education to gauge participants’ knowledge and comprehension of the educational content. The study targeted residents of the Kadewatan complex in Ambon City. The community demonstrated a heightened awareness of the crucial role of PHBS in daily life. Participants exhibited improved understanding and positive attitudes toward PHBS, aligning with environmental health principles and their impact on public health. The health promotion efforts raised awareness and fostered clean and healthy living behaviours within the community. Notably, students from the Faculty of Medicine at Pattimura University effectively applied Problem-Based Learning methods to address real-world challenges society faces.